A theory and practice of program development - Andrews, Derek (Formal approaches to computing and information technology., 1997)
A Theory and Practice of Program Development provides a comprehensive introduction to a formal software development method based on the specification language VDM-SL. The method starts with an abstract formal specification of a software system and uses a series of development steps that preserve correctness to produce an executable program. The development steps involve strategies and transformations to change an abstract specification into executable code - the method is both justified and explained mathematically.